تقرير الأمم المتحدة العالمي عن تنمية الموارد المائية لعام 2017 - United Nations Educational, Scientific; Cultural Organization (United Nations, 2017)
The 2017 edition of the United Nations World Water Development Report, entitled “Wastewater: The Untapped Resource”, demonstrates how improved wastewater management generates social, environmental and economic benefits essential for sustainable development and is essential to achieving the 2030 Agenda for Sustainable Development. In particular, the Report seeks to inform decision-makers, government, civil society and private sector, about the importance of managing wastewater as an undervalued and sustainable source of water, energy, nutrients and other recoverable by-products, rather than something to be disposed of or a nuisance to be ignored. The report’s title reflects the critical role that wastewater is poised to play in the context of a circular economy, whereby economic development is balanced with the protection of natural resources and environmental sustainability, and where a cleaner and more sustainable economy has a positive effect on the water quality.